2017
DOI: 10.5551/jat.36558
|View full text |Cite
|
Sign up to set email alerts
|

<i>Whitmania Pigra</i> Whitman Extracts Inhibit Lipopolysaccharide Induced Rat Vascular Smooth Muscle Cells Migration and their Adhesion Ability to THP-1 and RAW 264.7 Cells

Abstract: Aim: Atherosclerosis is a kind of chronic inflammatory disease. A crucial pathology change of atherosclerosis is the migration of activated VSMCs to the intima where they interact with leukocytes by expressing adhesion molecules, including intercellular cell adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1). Moreover, monocyte chemoattractant protein-1 (MCP-1) expressed by VSMCs plays an important role in recruiting monocytes and macrophages. Leech (Whitmania pigra Whitman) is a tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Though previous studies conducted in general population settings have failed to demonstrate any statistically significant association of VCAM-1 with CVD risk, an increased risk of CVD with elevated levels of VCAM-1 has been suggested, given that circulating levels of other soluble adhesion molecules (such as E-selectin, P-selectin, or ICAM-1) have been found to be positively and independently associated with CVD outcomes 16 , 19 24 ) . Indeed, the therapeutic effect of leech enzyme extract on atherosclerosis (a traditional Chinese medicine commonly used for treating CVD) has been shown to be manifested via inhibiting the expression of adhesion molecules such as ICAM-1 and VCAM-1 49 ) . The mechanistic pathways for the link between elevated VCAM-1 levels and its protective effect on the development of CVD are unclear, as increased expression of soluble adhesion molecules have been suggested to play a direct role in the pathogenesis of atherosclerosis 50 ) via endothelial dysfunction and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Though previous studies conducted in general population settings have failed to demonstrate any statistically significant association of VCAM-1 with CVD risk, an increased risk of CVD with elevated levels of VCAM-1 has been suggested, given that circulating levels of other soluble adhesion molecules (such as E-selectin, P-selectin, or ICAM-1) have been found to be positively and independently associated with CVD outcomes 16 , 19 24 ) . Indeed, the therapeutic effect of leech enzyme extract on atherosclerosis (a traditional Chinese medicine commonly used for treating CVD) has been shown to be manifested via inhibiting the expression of adhesion molecules such as ICAM-1 and VCAM-1 49 ) . The mechanistic pathways for the link between elevated VCAM-1 levels and its protective effect on the development of CVD are unclear, as increased expression of soluble adhesion molecules have been suggested to play a direct role in the pathogenesis of atherosclerosis 50 ) via endothelial dysfunction and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Although NF‐κB has a central role in monocyte adhesion to the vascular endothelium via transcription of inflammatory mediators, multiple lines of study suggest that MAPKs also play an important role in NF‐κB‐dependent and ‐independent adhesion events in early atherosclerosis. A recent study showed that Whitmania pigra Whitman suppresses the expression of adhesion molecules (e.g., ICAM‐1 and VCAM‐1), the phosphorylation of p38, and p65 nuclear localization (Li et al, 2017). Liu et al suggested that matrine downregulates IkBα phosphorylation, which inhibits the expression of adhesion molecules including VCAM‐1 and ICAM‐1 by suppressing MAPKs and p65 translocation from the cytosol to the nucleus (Liu et al, 2016).…”
Section: Nutraceuticals Can Prevent Monocyte Adhesion To the Endotheliummentioning
confidence: 99%
“…Aconiti Lateralis Radix Praeparata shows a significant effect in rheumatoid arthritis by inhibiting the concentrations of IL-1β, TNF-α, and IFN-γ [18]. Whitmania pigra Whitman has been widely employed in decoction for the treatment of blood stasis syndrome for many years in China and its enzyme extracts suppress LPS-induced upregulation of inflammatory factors in rat vascular smooth muscle cells [19]. These pre-clinical and clinical studies indicated that some herbs of SHG could directly kill bacteria and inhibit viruses while other herbs could regulate inflammation response and maintain a balance between pro-inflammatory and anti-inflammatory mediators, with no serious adverse reactions observed [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%